Molecular epidemiology of Clostridium difficile isolated from piglets - Putsathit, Papanin; Neela, Vasantha Kumari; Sither Joseph Vesudian, Narcisse Mary; Ooi, Peck Toung; Ngamwongsatit, Bhunika; Knight, Daniel R.; Riley, Thomas V. (Elsevier, 2019)
Information on the epidemiology of C. difficile infection (CDI) in South-East Asian countries is limited, as is data on possible animal reservoirs of C. difficile in the region. We investigated the prevalence and molecular epidemiology of C. difficile in piglets and the piggery environment in Thailand and Malaysia. Piglet rectal swabs (n = 224) and piggery environmental specimens (n = 23) were collected between 2015 and 2016 from 11 farms located in Thailand and Malaysia. All specimens were tested for the presence of C. difficile with toxigenic culture. PCR assays were performed on isolates to determine the ribotype (RT), and the presence of toxin genes. Whole genome sequencing was used on a subset of isolates to determine the evolutionary relatedness of RT038 (the most prevalent RT identified) common to pigs and humans from Thailand and Indonesia. C. difficile was recovered from 35% (58/165) and 92% (54/59) of the piglets, and 89% (8/9) and 93% (13/14) of the environmental specimens from Thailand and Malaysia, respectively. All strains from Thailand, and 30 strains from Malaysia (23 piglet and 7 environmental isolates) were non-toxigenic. To our knowledge, this is the first and only report with a complete lack of toxigenic C. difficile among piglets, a feature which could have a protective effect on the host. The most common strain belonged to RT038 (ST48), accounting for 88% (51/58) of piglet and 78% (7/9) of environmental isolates from Thailand, and all 30 isolates tested from Malaysia. Piglet RT038 isolates from Thailand and Malaysia differed by only 18 core-genome single nucleotide variants (cgSNVs) and both were, on average, 30 cgSNVs different from the human strains from Thailand and Indonesia, indicating a common ancestor in the last two decades.